Trabecular bone score in thais with or without type 2 diabetes - Hataikarn Nimitphong (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2020. Background: When compared to people without type 2 diabetes mellitus (T2DM), people with T2DM have an increase in fracture risk despite having higher bone mineral density (BMD). Many studies in Caucasians demonstrated that trabecular bone score (TBS) is lower in people with T2DM than those without. The utility of TBS as a fracture risk assessment tool in Asians with T2DM is currently unclear. Objective: To compared lumbar spine (LS) BMD and TBS in Thais with or without T2DM and investigate the correlation between TBS and hemoglobin A1c (HbA1c) and diabetes duration in participants with T2DM. Materials and Methods: The present study was a cross-sectional study that included 97 participants with T2DM (37 men and 60 women) and 342 participants without T2DM (174 men and 168 women). LS-BMD and TBS were obtained. Results: Men and women with T2DM were older and had higher body mass index (BMI). Men with T2DM had significant higher LS-BMD (1.051±0.166 versus 0.972±0.125, p=0.009) and non-significant lower TBS (1.333±0.084 versus 1.365±0.096, p=0.055) than those without. Similarly, women with T2DM had significant higher LS-BMD (0.995±0.155 versus 0.949±0.124, p=0.021) and lower TBS (1.292±0.105 versus 1.382±0.096, p<0.001). After adjusting for age and BMI, T2DM predicted higher BMD in men (p<0.001), but not in women (p=0.143). T2DM was not associated with TBS after adjusting for age and BMI in both genders (p=0.403 and p=0.151 in men and women, respectively). TBS did not correlate with HbA1c in both genders. However, TBS was non-significantly associated with diabetes duration in women (p=0.073), but not in men (p=0.639). Conclusion: T2DM significantly predicted higher LS-BMD only in men and was not independently associated with TBS in both genders. These data highlighted that, in T2DM, there was some variation in the clinical usefulness of BMD and TBS in predicting osteoporotic fractures with regard to clinical characteristic of participants.